2019
DOI: 10.1109/jetcas.2019.2898768
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Open-Source Static 3D Mesh Codecs for Immersive Media Interactive Live Streaming

Abstract: This work provides a systematic understanding of the requirements of live 3D mesh coding, targeting (tele-)immersive media streaming applications. We thoroughly benchmark in rate-distortion and runtime performance terms, four static 3D mesh coding solutions that are openly available. Apart from mesh geometry and connectivity, our analysis includes experiments for compressing vertex normals and attributes, something scarcely found in literature. Additionally, we provide a theoretical model of the tele-immersion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Nevertheless, only some of these studies considered the stateof-the-art compression methods in a way which can be beneficial for a VV setting. Doumanoglou et al [22] and Christaki et al [23] studied different open source mesh compression algorithms and found Google's Draco the best performing among the compared. Su et al [12] used static point clouds to compare three different encoders: L-PCC, S-PCC, and V-PCC.…”
Section: Related Workmentioning
confidence: 99%
“…Nevertheless, only some of these studies considered the stateof-the-art compression methods in a way which can be beneficial for a VV setting. Doumanoglou et al [22] and Christaki et al [23] studied different open source mesh compression algorithms and found Google's Draco the best performing among the compared. Su et al [12] used static point clouds to compare three different encoders: L-PCC, S-PCC, and V-PCC.…”
Section: Related Workmentioning
confidence: 99%
“…Mesh streaming (loading of only necessary mesh data instead of loading the whole mesh) can also be used, but most existing solutions propose only mesh transfer over the network [Kim04]. Partial load of mesh data from external storage to RAM for more effective processing (including compression) is also described [Ise05], but in all cases only the decompressed mesh is used during rendering [Dou19].…”
Section: Existing Solutionsmentioning
confidence: 99%
“…So far, many mesh compression algorithms have been proposed, e.g., Corto [24], Google Draco [25], O3dgc [26], and OpenCTM [27]. We decided to use Google Draco, an open-source library developed by Google, because it is one of the most efficient and fastest algorithms according to recent benchmarking studies [28] and also our experiments. In the following, Draco's core blocks are described.…”
Section: Mesh Compressionmentioning
confidence: 99%